Benthic‐pelagic coupling drives non‐seasonal zooplankton blooms and restructures energy flows in shallow tropical lakes. (18th March 2016) - Burian, Alfred; Schagerl, Michael; Yasindi, Andrew; Singer, Gabriel; Kaggwa, Mary Nakabungo; Winder, Monika
Abstract: Zooplankton blooms are a frequent phenomenon in tropical systems. However, drivers of bloom formation and the contribution of emerging resting eggs are largely unexplored. We investigated the dynamics and the triggers of rotifer blooms in African soda‐lakes and assessed their impact on other trophic levels. A meta‐analysis of rotifer peak densities including abundances of up to 6 × 10 5 individuals L −1 demonstrated that rotifer bloom formation was uncoupled from the food environment and the seasonality of climatic conditions. A time series with weekly sampling intervals from Lake Nakuru (Kenya) revealed that intrinsic growth factors (food quality and the physicochemical environment) significantly affected rotifer population fluctuations, but were of minor importance for bloom formation. Instead, rotifer bloom formation was linked to sediment resuspension, a prerequisite for hatching of resting‐eggs. Population growth rates exceed pelagic birth rates and simulations of rotifer dynamics confirmed the quantitative importance of rotifer emergence from the sediment egg‐bank and signifying a decoupling of bloom formation from pelagic reproduction. Rotifer blooms led to a top‐down control of small‐sized algae and facilitated a switch to more grazing‐resistant, filamentous cyanobacteria. This shift in phytoplankton composition cascaded up the food chain and triggered the return of filter‐feeding flamingos. Calculations of consequent changes in the lake's energy budget and export of aquatic primary production to terrestrial ecosystems demonstrated the large potential impact of nonseasonal disturbances on the functioning of shallow tropical lakes.